Pemakaian Natrium Karbonat Pada Pencapan Alkali-Discharge dengan Zat Warna Dispersi pada Kain Poliester - Luciana Luciana (Universitas Insan Cendekia Mandiri, 2020)
Polyester fabrics are the most popular clothing material in the textile product manufacturing process and are widely used. Small floral motifs, line or small dots that are sharp and bright (more than one color) on the basis of contrasting or dark colors usually obtained by discharge printing or resist printing, because it is not easy to do by direct printing in a large amount of production. In printing alkali discharge, polyester fabrics are used dispersion dyes that can be damaged by alkali (azo type) as the base color. Color motifs are used dispersion dyes that are resistant to alkalis (anthraquinone type) which do not have ester groups in their chromophore. The purpose of this study was to determine the extent to the influence of the concentration of using sodium carbonate 100, 150, 200, 250 g/kg paste as etching agent and fixation time 4,6,8 minutes temperature 180 °C, then testing the degree of fabric white, color difference, fabric tensile strength and color fastness against washing and rubbing. The optimum conditions were achieved in sodium carbonate 200 g/kg paste, temperature 180 °C for 6 minutes, white degree of fabric Δ K/S 0.01684, color difference value Δ E= 2,81, fabric tensile strength of 17,40 kg towards warp 18,05 kg towards the feed, fastness to washing 4-5, color fastness to wet rubbing and dry rubbing 4-5. Keywords : sodium carbonate, discharge printing, azo, anthraquinone, polyester